A comparative study of online and face-to-face gatekeeper training using the suicide CARE program - Lee, Ah Rah; Choi, Sung Moon; Lee, Hwa-Young; Kim, Soung Nam; Lim, Jeungsuk; Lee, Sang Min; Paik, Jong-Woo (Frontiers in Psychiatry, 2025)
BackgroundGatekeeper training programs are essential public health strategies for suicide prevention. With the rapid digitization of health education, evaluating the effectiveness of online gatekeeper training relative to traditional face-to-face training has become increasingly important.ObjectivesThis study compared the effectiveness of online and face-to-face formats of the standardized Suicide CARE 2.0 gatekeeper training in enhancing suicide prevention knowledge, attitudes, behaviors, and preparedness among community mental health workers in South Korea. We tested the non-inferiority of the online format in improving key outcomes.MethodsA quasi-experimental, two-group pre–post design was employed with 99 participants (51 face-to-face, 48 online) recruited from community mental health centers. Participants were randomly assigned to either the online or face-to-face gatekeeper training group using a computerized randomization tool (www.randomizer.org). Both groups received identical content delivered by the same instructor. Outcomes assessed included self-perceived knowledge, factual knowledge, preparedness to help, attitudes toward suicide, and suicide prevention behaviors. Analyses included paired t-tests and ANCOVA, with effect sizes (Cohen’s d, partial η²) and 95% confidence intervals reported.ResultsBoth groups significantly improved all five domains. The online group showed greater improvements in self-perceived knowledge, preparedness, and behaviors (p < 0.001), while the face-to-face group demonstrated larger gains in factual knowledge (p = 0.017). Effect sizes supported the practical relevance of these findings. Both groups exhibited positive shifts in attitudes, with the online group showing more pronounced changes in avoidant attitudes and readiness to intervene. However, changes in deeply entrenched beliefs, such as the normalization of suicide, were limited.ConclusionOnline gatekeeper training is a feasible and effective alternative to face-to-face instruction, particularly in settings with limited resources or during emergencies. While each format offers distinct advantages, hybrid models may yield the most comprehensive benefits. These findings support the inclusion of scalable online training in national suicide prevention strategies. Suicide prevention, gatekeeper training, Suicide CARE, online education, face-to-face education, and community mental health.